A multivalent T-antigen-based vaccine for Group A Streptococcus - Jacelyn M. S. Loh (Nature Portfolio, 2021)
Abstract Pili of Group A Streptococcus (GAS) are surface-exposed structures involved in adhesion and colonisation of the host during infection. The major protein component of the GAS pilus is the T-antigen, which multimerises to form the pilus shaft. There are currently no licenced vaccines against GAS infections and the T-antigen represents an attractive target for vaccination. We have generated a multivalent vaccine called TeeVax1, a recombinant protein that consists of a fusion of six T-antigen domains. Vaccination with TeeVax1 produces opsonophagocytic antibodies in rabbits and confers protective efficacy in mice against invasive disease. Two further recombinant proteins, TeeVax2 and TeeVax3 were constructed to cover 12 additional T-antigens. Combining TeeVax1–3 produced a robust antibody response in rabbits that was cross-reactive to a full panel of 21 T-antigens, expected to provide over 95% vaccine coverage. These results demonstrate the potential for a T-antigen-based vaccine to prevent GAS infections.